Allelopathic potential of Asystasia gangetica: A study on growth and production of sweet corn - Roelly Ainul Yaqin; Edi Santosa; Dwi Guntoro (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2024)
Coromandel, or Chinese violet (Asystasia gangetica), is an invasive weed on many plantations in Indonesia, especially oil palm plantations. The A. gangetica is suspected to produce allelopathic compounds. However, the evaluation of the effect of A. gangetica on plant growth is still rare. The research objective was to evaluate the effect of allelopathic compounds of A. gangetica on the growth and production of sweet corn as a test plant. An experiment with a randomized complete block design and four replications was conducted from March to September 2022 at the Agribusiness and Technology Farm IPB. The treatment was the A. gangetica population consisted of 0 (control), 1, 2, 4, 8, and 16 individuals per pot. A. gangetica were initially planted from seeds, and the stems were slashed 5 cm above the soil surface two months after planting. One week after cutting, sweet corn seeds were planted and maintained until harvest 72 days after planting. The results showed that the allelopathic effect of A. gangetica was evident in growth of sweet corn plant. Increasing number of A. gangetica per pot increased the allelopathic effect. The most significant effect was from 16 populations per pot, which significantly reduced the growth of sweet corn height, stem diameter, leaf size (length and width), leaf number, and color. The particular population per pot also decreased sweet corn yield, i.e., weight per cob with and without husk, and cob diameter by 18.95%, 22.0%, and 19.37%, respectively. The level of sweetness decreased by 31.24% after sweet corn was planted in the remnant of 16 individuals A. gangetica per pot. Nevertheless, A. gangetica did not significantly affect leaf area index, cob length, and sweet corn biomass, including shoot and root dry weight at harvest. It would be interesting to evaluate the effect of A. gangetica in the field. Keywords: allelopathy; Brix; indole-3-carboxaldehyde; secondary metabolites; weeds